Formulation and Evaluation of Spirulina-Based Gel with Varying Carbopol Concentrations for Anti-Acne Activity against Staphylococcus epidermidis - Emmellia Yunitha; Anita Nilawati; Mega Novita; Dian Marlina (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Spirulina platensis is a blue-green microalga known for its antibacterial properties, offering potential as a natural alternative in acne treatment. Acne vulgaris, often caused by Staphylococcus epidermidis, requires effective topical solutions. Gels are favored for their non-greasy texture, ease of application, and good skin absorption. This study aimed to formulate and evaluate anti-acne gels containing 25% Spirulina extract with varying Carbopol concentrations (0.5%, 1%, 1.5%). Each formulation was assessed for physical properties, stability over 21 days, and antibacterial activity against S. epidermidis. All gel formulations met quality standards for pH, homogeneity, viscosity, spreadability, and adhesiveness. The gel with 0.5% Carbopol (FI) showed the best spreadability, ideal viscosity, and good adhesiveness, along with the highest antibacterial activity, exhibiting an inhibition zone of 16.5 mm—comparable to tetracycline. In conclusion, Spirulina-based gel with 0.5% Carbopol offers an effective, stable, and natural anti-acne option. These findings highlight the potential of Spirulina as a bioactive agent in topical formulations and encourage further research for clinical applications in acne management.